Characteristics of frozen-thawed semen on Simmental and Limousin bulls in Ungaran, Indonesia - Triva Murtina Lubis; Prabowo Purwono Putro; Aris Junaidi; . Hamny (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
The present research aimed to study the characteristics of frozen-thawed semen in beef bulls ex-import in Ungaran, Indonesia. 5 heads Simmental and 5 heads Limousin of 5.5 years old were used in this research. The research was done in Ungaran Artificial Insemination Center, Central Java, Indonesia and Laboratory of Reproduction and Obstetry, Faculty of Veterinary Medicine, Gadjah Mada University, Yogyakarta, Indonesia. Frozen semen was obtained from this AI center. Results of the research indicated that the average individual motility of Simmental and Limousin is 39.00±5.48% and 36.00±2.24%. The average percentage of live spermatozoa is 54.00±10.75% for Simmental and 48.20±9.78% for Limousin while  the average proportion of abnormal spermatozoa is 9.60±3.36% and 6.80±4.15% for both Simmental and Limousin, respectively. On average, Simmental frozen-thawed semen have the higher mean proportion of sperm motility, live sperm, and abnormal sperm than that of Limousin frozen-thawed semen